"911 What's Your Emergency?": Deception in 911 Homicide and Homicide Staged as Suicide Calls. Issue 3 (August 2021) - Miller, Michelle L.; Merola, Melissa A.; Opanashuk, Leonard; Robins, Cari J.; Chancellor, Arthur S.; Craun, Sarah W.
Emergency 911 calls are often the first indication a homicide occurred and serve as initial witness statements in an investigation. The current study explores deception among homicide and homicide staged as suicide 911 calls. One hundred suicides, 18 homicide staged as suicide calls, 31 homicides with uninvolved callers, and 26 homicide offender calls were compared. Little overlap was found in deception indicators between the current findings and previous studies. Caution is warranted when extrapolating from studies using only 911 homicide calls to equivocal death cases, where investigators consider if the manner of death is a suicide or a staged homicide.